Patterns of sedentary behaviour and physical activity in people following curative intent treatment for non-small cell lung cancer - Cavalheri, Vinicius; Jenkins, Susan; Cecins, N.; Phillips, M.; Sanders, L.; Hill, Kylie (Sage Publications Ltd., 2016)
This study aimed to compare patterns of sedentary behaviour (SB) and physical activity (PA) in people following curative intent treatment for non-small cell lung cancer (NSCLC) with healthy controls. Participants 6-10 weeks following lobectomy for NSCLC and healthy controls wore two activity monitors for 7 days. Waking hours were divided into time spent in SB (<1.5 metabolic equivalent of tasks (METs)), light intensity PA (LIPA ≥ 1.5 to <3.0METs) and moderate-to-vigorous intensity PA (≥3.0METs). Daily steps were also recorded. Data were available in 20 participants with NSCLC (13 females; 68 ± 10 years) and 20 healthy controls (13 females; 69 ± 5 years). The NSCLC group accumulated a greater percentage of time in SB in uninterrupted bouts ≥30 minutes (49% vs. 42%; p = 0.048). Further, the NSCLC group spent a lower percentage of waking hours in LIPA (21 ± 9% vs. 26 ± 8%; p = 0.04) and accumulated a lower percentage of time in this domain in uninterrupted bouts ≥10 minutes (13% vs. 19%; p = 0.025). The NSCLC group also had a lower daily step count (8863 ± 3737 vs. 11,856 ± 3024 steps/day; p = 0.009). Time spent in moderate-to-vigorous intensity PA was similar in both groups (p = 0.92). People following curative intent treatment for NSCLC spend more time in prolonged bouts of SB at the expense of LIPA.